Penggunaan Model Pembelajaraan Bamboo Dancing Dalam Meningkatkan Hasil Belajar IPS Siswa Kelas 5 SD - Riani Ayu Utami; Nyoto Harjono (Universitas Ngudi Waluyo, 2019)
The purpose of this study was to determine the effect of learning model bamboo dancing or dance bamboo on the result of study social scienceÂ student of class V elementary school. This study uses the method of meta-analysis. After doing the calculation, the results of the study showed an increase learning outcomes social science student of class V by using the learning model bamboo dancing or dance bamboo ranging from a low of 19,53% to a high of 113% with an average 54,54%. It can be concluded that learning model bamboo dancing or dance bamboo can improve learning outcomes social science student of class V elementary school.